The NILAI-NILAI ESTETIS PADA ORNAMENT-ORNAMENT MESJID TARBIYAH MEDAN-SUMATERA UTARA - Ratu Alifah Nasyaa; Mulyadi Mulyadi (Yayasan Haiah Nusratul Islam, 2024)
Tarbiyah Mosque is one of the mosques that has many calligraphic writings. With this, researchers took action to examine the aesthetic value of mosque ornaments, Ornamental calligraphy is the art of writing calligraphy, This research was conducted using qualitative methods to get the researcher closer to the subject. and researchers conducted interviews to find out the benefits of calligraphy on Medan Tarbiyah mosque’s ornaments. The results of this study show that the calligraphy in the tarbiyah mosque ornaments uses a lot of khaṭ ṣulūṣ and Kūfī. With its beautiful and diverse coloring and writing, it turns out that in reality it is not necessarily able to make worshipers willing to read and understand the meaning of the writing. However, the writings written by the architect are the writings that Muslims usually say in their prayers. Calligraphic writing on tarbiyah mosque ornaments can be understood and read because it is part of the prayer sentence that Muslims often say.